Emotional Intelligence Profiles and Cyber-Victimization in Secondary School Students: A Multilevel Analysis - Francisco Villegas-Lirola (MDPI AG, 2024)
The research examined how different profiles of emotional intelligence (attention, clarity, and emotional regulation) act as protective or risk factors against cyber-victimization, taking into account individual and behavioral variables such as gender, sexual orientation, self-esteem, social anxiety, Internet risk, and parental control among high school students (11-18 years). A simulated sample was used, which was derived from an experimental sample of 1908 subjects (50.7% girls). Statistical equivalence was ensured between the two samples, and a multilevel analysis was conducted using the emotional intelligence profiles as the grouping variable. The results showed that the variability in emotional intelligence profiles predicted 96.7% of the variability of cyber-victimization. Factors that increase this likelihood include excessive interpersonal attention and low emotional regulation, higher social anxiety, offline victimization, older age, high parental supervision, and low self-esteem. In addition, being male and heterosexual is associated with a lower risk of cyber-victimization than being female and non-heterosexual. In general, it is suggested that protective measures against cyber-victimization should warn about the risk of Internet use, avoid paternalistic behavior by adults, and reduce rumination or excessive attention to the opinions of others.